THE EFFECT OF FLAP POSTER ON STUDENTSâ CREATIVITY IN LEARNING HUMAN RESPIRATORY SYSTEM - Rahmawati, Juwita; Solihin, Hayat; Rusyati, Lilit (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2015)
This descriptive research investigated the influence of the flap poster on studentsâ creativity in studying human respiratory system. Samples were 34 eight grade students in one of Private International Schools in Bogor, in which they were divided into experimental or control class, 17 students for each class. Qualitative data were obtained by using rubric and questionnaire. Results showed that experimental class studentsâ creativity was higher than control class students, in which this indicates that flap poster can facilitate students in developing their creativity. Furthermore, results also indicated that when the flap poster was implemented in learning Human Respiratory concept, experimental class achieved better results in every creativity dimension compared to control class.Â ABSTRAKPenelitian deskriptif ini menyelidiki pengaruh penggunaan flap poster terhadap kreativitas siswa dalam mempelajari materi Sistem Pernapasan Manusia. Sampel adalah 34 siswa kelas delapan di salah satu sekolah swasta internasional yang ada di Bogor. Siswa kemudian dibagi menjadi kelompok eksperimen dan kontrol dengan 17 siswa untuk masing-masing kelas. Data kualitatif diperoleh dengan menggunakan rubrik dan kuesioner. Hasil menunjukkan bahwa siswa di kelas eksperimen memiliki kreativitas yang lebih tinggi dibandingkan dengan kelas kontrol, dan ini mengindikasikan bahwa flap poster dapat memfasilitasi siswa dalam mengembangkan kreativitasnya. Selain itu, hasil juga mengindikasikan bahwa ketika flap foster diimplementasikan dalam mempelajari konsep Pernapasan Manusia, kelas eksperimen meraih hasil yang lebih baik dalam semua dimensi kreativitas dibandingkan dengan kelas kontrol.